Implementasi Metode Simple Additive Weighting Untuk Seleksi Penerimaan Beasiswa - Joko Kuswanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
One factor that can support student enthusiasm for learning is the existence of educational assistance in the form of scholarships. Various types of scholarships are given to students who have achievements both academic and non-academic achievements. Conditions that often occur in the process of awarding scholarships, the assessment is not always decided based on definite considerations and predetermined criteria. The process of determining the provision of scholarships to students will be more effective and efficient if you use a decision support system. With the existence of a decision support system, it can help the selection team in the selection process of scholarship recipients so as to speed up the decision-making process based on predetermined criteria. The decision support system to be built applies the Simple Additive Weighting (SAW) method. With the new system, it is expected to help the selection team related to managing applicant data, selection and proposal of scholarship recipients can be done more easily and quickly.